Pengaruh Kepribadian Proaktif Terhadap Kinerja Guru Yang Dimediasi Organizational Citizenship Behavior Pada Guru Di SMA Montessori - Latifa Kamilatunnisa; Adhitya Yoga Prasetya (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2024)
The purpose of this study was to analyze the influence of proactive personality, OCB on teacher performance at Montessori Kaloran High School Using census techniques, the number of samples used was equal to the total population of 35 respondents. By using Smart PLS to analyze data is outer loading, inner model and hypothesis testing Then the results showed that 1) proactive personality has a significant positive effect on OCB, 2) OCB has no significant effect on performance,3) Proactive personality has a significant positive effect on performance, and 4) OCB is not a mediation between proactive personality and teacher performance.